Ageing / Loan Davies. - Davies, loan. (London : the camelot press, 1983)
Contributed articles.
Includes bibliographical references and index.
Keywords: Older people -- India -- Social conditions; Older people -- Health and hygiene -- India; Aging -- Social aspects -- India